Eu quero entrar: processos que (des)constroem o acesso de pessoas trans aos serviços de saúde bucal - Brum, Valquíria Martins de (2023)
Transgender is anyone who has an identity other than the sex assigned at birth. It is an umbrella designation that encompasses different identities, which differ according to territory, culture and historical moment. There are no official surveys to know this population, the studies vary in approach. About oral health, little is known about the situation that crosses this population, and there is only one brazilian study that addresses access to services and the perception of oral health of transgender people. Thus, this study seeks to investigate the processes that involve access to oral health services by transgender people in a medium-sized city in southern Brazil. This work is descriptive, qualitative and transversal. The collect was carried out using a focus group and the analysis through content analysis, with snowball sampling. Participated 10 trans people, being 05 trans men, 02 trans women, 01 non-binary trans woman and 02 non-binary people. More than half of the people (n = 08) have completed at least high school. In the group interviews, two topics emerged: the factor that determines access to oral health services and the factors that condition it. As a determinant, there is pain, being the conditioning factors: financial conditions, respect for the name, previous experiences with oral health services and expectations about gender expression. The processes that cross access to oral health services by transgender people reflect the need to guarantee rights, such as the rectification of documents, work and study opportunities and support from health services and society.